Evaluating the Effectiveness of Benguet Pine (Pinus kesiya) Xylem for Deep Well Water Filtration - Hizon, Allen Conner C. (Animo Repository, 2024)
Even today, many rural and remote communities still do not have access to safe drinking water, which is a basic right of every human. To address this problem, the effectiveness of the Benguet pine tree (Pinus kesiya) xylem as a sustainable water filtration method for well water was investigated. The physical and chemical properties of the filtered and unfiltered deep well water were tested: the total dissolved solids (TDS) and the electrical conductivity using a 5-in-1 electronic water quality tester and the pH level using pH strips. On the other hand, the microbiological metrics, such as heterotrophic plate count (HPC) and the total coliform count, were tested using the Pour Plate Method and the Multiple Tube Fermentation Technique, respectively. The properties of both water samples were compared with each other and with the acceptable values. The results show that the two water samples contain TDS and pH within acceptable levels. Notably, the Benguet pine tree xylem is highly effective at filtering the deep well water and lowering TDS (M=84.7, SD=7.50), electrical conductivity, and HPC (M=325, SD=31.1) within acceptable levels without affecting the pH level, but demonstrated limited effectiveness in removing microorganisms such as coliforms. Furthermore, it can filter 52.9 mL of deep well water every hour. Overall, the results suggest that the Benguet pine tree xylem has the potential to improve the deep well water quality significantly. While these findings highlight the potential of the Benguet pine tree xylem for addressing specific physical water quality parameters, further research is necessary to enhance its overall water treatment capabilities in filtering coliforms and explore its applicability in diverse water quality conditions.